Poly(methyl methacrylate)‐Assisted Exfoliation of Graphite and Its Use in Acrylonitrile‐Butadiene‐Styrene Composites. Issue 29 (17th April 2020) - Gentiluomo, Silvia; Thorat, Sanjay B.; Del Río Castillo, Antonio Esau; Toth, Peter S.; Panda, Jaya Kumar; Pellegrini, Vittorio; Bonaccorso, Francesco
Abstract: One of the applications of graphene in which its scalable production is of utmost importance is the development of polymer composites. Among the techniques used to produce graphene flakes, the liquid‐phase exfoliation (LPE) of graphite stands out due to its versatility and scalability. However, solvents suitable for the LPE process are generally toxic and have a high boiling point, making the processing challenging. The use of low boiling point solvents could be convenient for the processing, due to the easiness of their removal. In this study, the use of poly(methyl methacrylate) (PMMA) as a stabilizing agent is proposed for the production of graphene flakes in a low boiling point solvent, that is, acetone. The graphene dispersions produced in the mixture acetone‐PMMA have higher concentration, +175 %, and contain a higher percentage of few‐layer graphene flakes (<5 layers), that is, +60 %, compared to the dispersions prepared in acetone. The as‐produced graphene dispersions are used to develop graphene/acrylonitrile‐butadiene‐styrene composites. The mechanical properties of the pristine polymer are improved, that is, +22 % in the Young's modulus, by adding 0.01 wt. % of graphene flakes. Moreover, a decrease of ≈20 % in the oxygen permeability is obtained by using 0.1 wt. % of graphene flakes filler, compared to the unloaded matrix. Abstract : Making graphene flakes : This study presents the exfoliation of graphite in acetone, by using poly(methyl methacrylate) (PMMA) as a stabilizing polymer, to produce few‐layer graphene (FLG). The presence of PMMA improves the liquid‐phase exfoliation (LPE) process, allowing to obtain thinner flakes, by hindering the flakes aggregation and increasing the FLG concentration, compared to dispersions, for example, in acetone (+175 %).